2020
DOI: 10.3390/ijms21249457
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Circulating Tumor Cells, Circulating Tumor DNA, and Exosomes in Breast Cancer Liquid Biopsies

Abstract: Breast cancer is the most common cancer among women worldwide. Although the five-, ten- and fifteen-year survival rates are good for breast cancer patients diagnosed with early-stage disease, some cancers recur many years after completion of primary therapy. Tumor heterogeneity and clonal evolution may lead to distant metastasis and therapy resistance, which are the main causes of breast cancer-associated deaths. In the clinic today, imaging techniques like mammography and tissue biopsies are used to diagnose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 148 publications
0
51
0
Order By: Relevance
“…to date, emerging studies have attempted to construct novel and effective strategies to address the deficiencies of accuracy and precision. The tentative methods includes the risk model based on tumor-specific ncRNAs patterns/signatures, the exosome-based tumor recognition, the immune infiltration characteristics, the genome-wide expression and somatic mutation analysis (19,20). These methods could serve as complementary or alternative prediction platforms with the conventional prediction method.…”
Section: Discussionmentioning
confidence: 99%
“…to date, emerging studies have attempted to construct novel and effective strategies to address the deficiencies of accuracy and precision. The tentative methods includes the risk model based on tumor-specific ncRNAs patterns/signatures, the exosome-based tumor recognition, the immune infiltration characteristics, the genome-wide expression and somatic mutation analysis (19,20). These methods could serve as complementary or alternative prediction platforms with the conventional prediction method.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported heterogeneity of PIK3CA mutations between tumor tissue and liquid biopsy. Beaver et al reported that none of the non-metastatic patients without PIK3CA mutation had detectable PIK3CA mutations in pre-surgery ctDNA 13 . Conversely, for metastatic diseases, Nakauchi et al…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy, which analyzes plasma-derived circulating tumor DNA (ctDNA), offers less-invasive and real-time insight into genetic alterations 12 . Recently, exosomes are a distinct source of tumor DNA that may be complementary to conventional liquid biopsy DNA sources 13,14 . In this study, we aimed to detect PIK3CA mutations through liquid biopsy using ctDNA in patients with metastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CTCs are poured into the bloodstream from primary or secondary tumor sites, and despite their very small number with a frequency of approximately 1-10 tumor cells in 10 6 -10 8 white blood cells, they are potentially able to give origin to distant metastases [18]. The identification and isolation of CTCs, especially in patients with early-stage disease, are closely related to the sensitivity and specificity of the isolation methods, usually consisting of sophisticated procedures including preliminary enrichment and subsequent isolation steps [16,19]. Numerous studies on breast, gastrointestinal, lung, skin, and prostate malignancies have shown that a CTC count above cut-off values between 3 and 5 CTCs/7.5 mL blood, determined by using the CellSearch platform, is associated with shorter progressionfree survival (PFS) and overall survival (OS) [16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these methods, there are many others, even more innovative, that still require clinical validation and analytical standardization. For instance, cancer cells are known to release "extracellular vesicles" (EV) into the circulation, which carry key elements, such as DNA, messenger RNA (mRNA), microRNA, and proteins, useful to investigate tumor characteristics since its very earliest stages [16,19,25].…”
Section: Introductionmentioning
confidence: 99%